2011
DOI: 10.1590/s1982-56762011000500002
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of a transposase sequence in Moniliophthora perniciosa confirms the occurrence of two genotypes in Bahia, Brazil

Abstract: Transposase sequence analysis is an important technique used to detect the presence of transposable elements in a genome. Putative transposase sequence was analyzed in the genome of the phytopathogenic fungus Moniliophthora perniciosa, the causal agent of witches' broom disease of cocoa. Sequence comparisons of the predicted transposase peptide indicate a close relationship with the transposases from the elements of the Tc1-Mariner superfamily. The analysis of the distribution of transposase sequence was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Various transposase transcripts of the same family were identified due to intron retention/excision. Introns within class II DNA transposons have been reported in plant pathogens [ 31 , 32 ], and phylogenetic analysis of the Mariner-2_SS and Mariner-3_SS families demonstrated that elements that required the removal of the intron were ancestral. Therefore, the intron appeared to not be an evolved trait that was important to the element because it allowed the genome some control over transposition due to the dependence of the transposon on the host-splicing mechanism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various transposase transcripts of the same family were identified due to intron retention/excision. Introns within class II DNA transposons have been reported in plant pathogens [ 31 , 32 ], and phylogenetic analysis of the Mariner-2_SS and Mariner-3_SS families demonstrated that elements that required the removal of the intron were ancestral. Therefore, the intron appeared to not be an evolved trait that was important to the element because it allowed the genome some control over transposition due to the dependence of the transposon on the host-splicing mechanism [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those data have been used to propose (Andebrhan et al, 1999) and to corroborate the hypothesis (de Arruda et al, 2003a, b;Rincones et al, 2003) that the witches' broom outbreak in Bahia State occurred by two independent focal points of introduction. Moreover, a reverse transcriptase sequence, part of a putative gypsy-like retrotransposon, and a transposase sequence, belonging to the TC1-Mariner superfamily, also distinguished C-biotype isolates from Bahia in two genotypic groups (Pereira et al, 2007;Ignacchiti et al, 2011). Thus, some transposable elements appear to spread through the M. perniciosa genome in accordance with some chromosomal groups.…”
Section: Discussionmentioning
confidence: 99%